Expression of retinoic acid-binding proteins and retinoic acid receptors in sebaceous cell carcinoma of the eyelids. Issue 1 (December 2015) - Tsai, Yueh-Ju; Wu, Shu-Ya; Huang, Hsuan-Ying; Ma, David; Wang, Nan-Kai; Hsiao, Ching-Hsi; Cheng, Ching-Yi; Yeh, Lung-Kun
Abstract Background Sebaceous cell carcinoma of the eyelid is a malignant tumor. However, the pathoetiology of sebaceous cell carcinoma is not clear. Retinoic acid (RA) signaling is essential for skin epidermal differentiation including the eyelids. In this study, we investigate the expression of β-catenin, RA-binding proteins and RA receptors in sebaceous cell carcinoma of the eyelid and try to estimate their influence on its pathoetiology. Methods Retrospective, noncomparative, consecutive interventional case series. Sixteen cases of eyelid sebaceous gland carcinoma who received tumor excision at our hospital between 2001 and 2011 were included. Immunohistochemical staining for β-catenin, cellular retinoic acid binding protein 1 (CRABP1), cellular retinoic acid binding protein 2 (CRABP2), fatty acid-binding protein 5 (FABP5), retinoic acid receptors (RAR-α, −β, −γ), and retinoid X receptors (RXR-α, −β, −γ) was performed on tissue samples obtained from tumor excision. Results Of the 16 sebaceous cell carcinoma cases reviewed, six were male and 10 female. The mean follow-up period was 6.7 ± 3.66 years (range, 0.3–13 years). Of these 16 cases, the expression of β-catenin was significantly increased in sebaceous cell carcinoma cases. CRABP1 was similarly expressed in the sebaceous cell carcinoma and control groups. CRABP2 and FABP5 were expressed in hair follicles of lid skin in both groups, whereas the CRABP2 and FABP5 were aberrantly expressed in the tumor cells of the sebaceous glands. Notably, the expression of retinoic acid receptor (RAR-β) and retinoid X receptors (RXR-β, −γ) was significantly upregulated in sebaceous cell carcinoma of the eyelids. Conclusions Our findings indicate that retinoic acid signaling is related to the pathogenesis of sebaceous cell carcinoma of the eyelids.